Peran Metode Pembelajaran dalam Meningkatkan Kemampuan Berbicara pada Pembelajaran BIPA - Marlini; Abdul Azis (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to explore the challenges, the role of the curriculum, and instructional strategies in improving the speaking skills of BIPA learners. This research employs a qualitative descriptive approach, with data sources derived from academic literature (journals, books, and relevant research reports) as well as curriculum documents and related teaching practices. Data collection was conducted through document analysis, while data were analyzed using content analysis techniques, including data reduction, categorization, and thematic interpretation. The findings indicate that the main challenges in developing communicative competence include pragmatic limitations, cultural differences, and the lack of authentic practice in learning activities. The BIPA curriculum tends to emphasize formal linguistic aspects and has not fully supported the development of contextual communicative competence. Therefore, the role of teachers and instructional media is crucial in creating interactive and contextual learning environments. Effective strategies include interaction-based learning, the use of digital technology, and the integration of cultural contexts into speaking activities. The implications of this study highlight the importance of developing more communicative, adaptive, and practice-oriented curricula and teaching strategies to enhance learners’ speaking skills. However, this study is limited by its reliance on secondary data derived from literature, which may not fully represent real classroom conditions. Future research is recommended to adopt empirical approaches involving field data to obtain more comprehensive findings.